Merger profitability and trade policy; Fusionen und Handelspolitik - Steffen Huck; Kai A. Konrad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
We study the profitability and welfare effects of merger in a strategic trade policy environment. Merger changes the strategic trade policy equilibrium. We show that merger can be profitable and welfare enhancing here, even though it is not profitable in a laissez-faire economy. A key element is the change in the governments' incentives to give subsidies to their local firms. We apply the results to the merger between Boeing and McDonnell-Douglas, where subsidies are a constant matter of debate. Our theory explains why the merger was profitable for Boeing and McDonnell-Douglas, why Airbus Industries opposed the merger, why the US authorities agreed to the merger, and why the EU competition authorities opposed it. – – Wir betrachten die Profitabilität und die Wohlfahrtseffekte von Unternehmensfusionen in einer internationalen Welt, in der Staaten das Instrument strategischer Außenhandelspolitik nutzen. Die Rückwirkungen der Fusionen auf die Wahl der strategischen Außenhandelspolitik machen Fusionen von Unternehmen des gleichen Landes profitabel, selbst wenn diese Fusionen in einer Welt ohne Außenhandelssubventionen nicht profitabel wären. Diese Resultate können erklären, weshalb die Fusion zwischen Boeing und McDonnell-Douglas profitabel war, weshalb Airbus unter der Fusion leidet und weshalb die US-Wettbewerbsbehörde der Fusion gegenüber positiver eingestellt war als die europäische Wettbewerbsbehörde.
Keywords: D43; D44; F12; L11; L13; 330; Merger; strategic trade policy